Materials for neuromorphic computing - enhancing spin orbit torque efficiency through low energy mixed ion bombardment. - Shaik Muhammad Abdillah Bin Hanifah Marican (Nanyang Technological University, 2023)
The rapid advancement towards Artificial Intelligence through the 21st century begs the question of whether our current computing facility is able to fully meet the computing demands of the future. Indeed, as many have pointed out, the current computing architecture is soon to plateau, attributed to the inherent throughput limitations of the von Neumann architecture. In this thesis, we discuss the Neuromorphic computing paradigm – a brain-inspired computing framework that circumvents the von Neumann bottleneck through co-locating the memory and computing subsystems. We illustrate how non-volatile memory based on spintronics has potential applications (beyond consumer electronics) towards realising non volatile magnetic memory using Spin Orbit Torque (SOT). Here, we also delve into the physics of magnetic materials which facilitate SOT. This gives us the grounding to understand our investigation to enhance SOT using a novel method of low-energy mixed ion exposure. Our results with Pt/Co/W structures have shown significant positive enhancement toward SOT efficiency, which provides future researchers with an extra parameter to finely tune SOT in future work